Methodological issues in event-related fMRI - Murphy, Kevin (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Psychiatry, 2005)
Functional magnetic resonance imaging (fMRI) is a very powerful tool for localising psychological functions to specific brain areas. Recently, there has been a surge of interest in determining the functional differences that might characterise certain populations. However, the results of event-related fMRI can be questionable due to the complexities of the techniques involved. A researcher must eliminate possible between-group confounds and optimally design experiments to increase confidence in findings. Addressing some of these methodological concerns is the focus of this thesis. Four questions have been chosen that are of particular importance in event- related fMRI, but have been poorly investigated in the literature.
Keywords: Psychiatry, Ph.D.; Ph.D. Trinity College Dublin